2021
DOI: 10.3847/1538-4365/abcb81
|View full text |Cite
|
Sign up to set email alerts
|

OGLE-ing the Magellanic System: Optical Reddening Maps of the Large and Small Magellanic Clouds from Red Clump Stars

Abstract: We present the most extensive and detailed reddening maps of the Magellanic Clouds (MCs) derived from the color properties of Red Clump (RC) stars. The analysis is based on the deep photometric maps from the fourth phase of the Optical Gravitational Lensing Experiment (OGLE-IV), covering approximately 670 deg 2 of the sky in the Magellanic System region. The resulting maps provide reddening information for 180 deg 2 in the Large Magellanic Cloud (LMC) and 75 deg 2 in the Small Magellanic Cloud (SMC), with a re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 57 publications
1
85
1
Order By: Relevance
“…Studies in the literature show that 30 Dor and the central region of the LMC have higher reddening compared with the rest of the disc (e.g., Zaritsky et al 2004;Haschke et al 2011;Subramanian & Subramaniam 2013;Górski et al 2020;Skowron et al 2021;Grady et al 2021). Recent extinction maps of Mazzi et al (2021) based on star-formation history (SFH) studies using VMC data also support these previous findings.…”
Section: Impact Of Reddening and Distance Variationsmentioning
confidence: 70%
See 1 more Smart Citation
“…Studies in the literature show that 30 Dor and the central region of the LMC have higher reddening compared with the rest of the disc (e.g., Zaritsky et al 2004;Haschke et al 2011;Subramanian & Subramaniam 2013;Górski et al 2020;Skowron et al 2021;Grady et al 2021). Recent extinction maps of Mazzi et al (2021) based on star-formation history (SFH) studies using VMC data also support these previous findings.…”
Section: Impact Of Reddening and Distance Variationsmentioning
confidence: 70%
“…Nidever et al (2020) reported metallicities of 3600 RGB stars based on high-resolution H-band spectra from the APOGEE survey. Skowron et al (2021) used the APOGEE data of red giant (RG) stars from Nidever et al (2020) to estimate an LMC MG of −0.026±0.002 dex deg −1 out to around 8 • .…”
mentioning
confidence: 99%
“…There is the 2019 determination made by reference [81] which measures TRGB in a nine SNIa hosts, adds 5 from [80], and calibrates TRGB in the LMC which yields H 0 = 69.8 ± 0.8(stat) ± 1.7(sys) km s −1 Mpc −1 at 68% CL and reference [82] (F20), for which H 0 = 69.6 ± 0.8(stat) ± 1.7(sys) km s −1 Mpc −1 at 68% CL, or the same but with a different accounting of the LMC extinction of the TRGB using reddening maps derived from red clump stars by [83] gives H 0 = 72.4 ± 2.0 km s −1 Mpc −1 at 68% CL. A value of H 0 ∼ 72 km s −1 Mpc −1 also results from the revised OGLE Team LMC reddening maps [84,85]. The addition of two new TRGB measurements in NGC 1404 and NGC 5643, host to 4 SNIa [86] appears to raise the F20 value of H 0 by ∼1% to ∼70 km s −1 Mpc −1 but the revised value is not tabulated.…”
Section: Latementioning
confidence: 93%
“…For the Gaia photometry, we follow the dereddening procedure of Gaia Collaboration et al (2018a), using the first two terms in their Equation (1) to do so. The recent red clump calibration of Skowron et al (2021) has provided reddening maps for the LMC and SMC with good resolution in the central parts of the Clouds, regions where those of Schlegel et al (1998) suffer from high levels of dust. Consequently, we utilize these recent maps for the innermost regions of the Clouds.…”
Section: Datamentioning
confidence: 99%